The communist uprisings of 1926-1927 in Indonesia. Key documents. Ed and with an introd. by H.J. Benda and R.T. McVey (Southeast Asia Program Department of Far Eastern Sudies, Cornell University, 1960)
Translation series. Modern Indonesia Project.